2015
DOI: 10.1016/j.placenta.2015.07.122
|View full text |Cite
|
Sign up to set email alerts
|

MTA3 regulates differentiation of human cytotrophoblast stem cells

Abstract: Introduction Early placental development depends on the correct balance of cytotrophoblast (CTB) proliferation and differentiation, into either syncytiotrophoblast (STB) involved in nutrient/gas exchange, or invasive extravillous trophoblast (EVT) involved in establishment of blood flow to the placenta. Metastasis associated protein-3 (MTA3) is a transcriptional co-repressor known to regulate cell migration. In addition, MTA3 is reportedly decreased in preeclampsia. We set out to investigate the role of MTA3 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…In pre-eclampsia, the levels of MTA-3 appear to be reduced [ 35 ]. Therefore, when Horii et al generated MTA-3 stable knockdown in choriocarcinoma JEG-3 cells using shRNA, there was a 60% decrease in hCG secretion in the knockdown models compared to control, and migration was increased by 1.8-fold [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In pre-eclampsia, the levels of MTA-3 appear to be reduced [ 35 ]. Therefore, when Horii et al generated MTA-3 stable knockdown in choriocarcinoma JEG-3 cells using shRNA, there was a 60% decrease in hCG secretion in the knockdown models compared to control, and migration was increased by 1.8-fold [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 A). Owing to the recent finding that CTB proliferation and trophoblast stemness are responsible for early placental development [ 24 , 25 ], we next explored the role of ACTN4 in trophoblast proliferation. This was accomplished by treatment of the first trimester villous explants with a siRNA that specifically targeted the mRNA of ACTN4.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic reconstruction of epigenome happens in the trophoblast differentiation and function and chromatin remodeling proteins such as MTA3 are known to play important roles in this process [ 19 ]. MTA3 is a subunit of NuRD complex and is involved in the regulation of villous trophoblast differentiation and fusion [ 15 , 16 ]. In this study, we showed inhibition of MTA3 correlates with increased trophoblast invasion and up-regulated invasion-related genes MMP2 , MMP9 , and Snail in EVT cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we showed MTA3 regulates trophoblast gene expression in villous trophoblast [ 15 ]. A recent report identified MTA3 functions in stem cells [ 16 ]; MTA3 regulates the differentiation of cytotrophoblast stem cells into EVT cells [ 16 ]. However, the role of MTA3 and its related mechanisms in EVT, especially EVT invasion, is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%